MAPEAMENTO DA VULNERABILIDADE À POLUIÇÃO DO AQÜÍFERO RIO DA BATATEIRA, UTILIZANDO O MÉTODO GOD, CRATO-CE. - Tavares, P. R. L.; da Silveira, J. G. P.; da costa, C. T. F.; de Castro, M. A. H. (Águas Subterrâneas, 2008)
Indisponível